Application of finite differences for the flow of pollutants in the Ayamonte Aquifer - Romero Baylón, Alfonso (2012)
If we modelling the flux of subterranean waters in an aquiferous, implicitly modelling the flux of mobile polluting agents dissolves, keeping in mind this premise, our analysis of the flux of polluting agents in the aquiferous thing of Ayamonte, will remain represented in the study of the flux of the subterranean waters in a hydrogeological halfback regular guest and it provide with uniforms, agree that detail in the later analysis of this document. However, the treatment, must notice that for polluting in suspension and other type of polluting agents, the treatment it differs of the analysis that here carry out. By means of the application of the finite differences and the language of fortran programming for the solution of the flux and transports of polluting agents in water subterranean this work has developed in cabinet and excel. The method of used solution in the solution of this problem, it are the algorisms of polynomial interpolation of Neuton Gregoy, and for the solution of the equations with derived partial of Laplace, has used the algorism of derived first and second of Stirling with the method of the finite differences, moreover have added a modulate of program in fortran for linux platform, that consists in a routine of acceleration of the conditions of limits in the considerate differential equations for flux of subterranean waters. This method of solution is interactive and, approximates the partial differential equations through an approximate solution by means of the use of algorisms of solution. The model calculates has agreed for aquiferous in stable state, using the same static levels as initial condition, and keeping in mind the hydrogeological conceptual model ( bordered-gives birth) with remissive and coefficient of constant storage in a homogeneous halfback.